A League of their Own: Female Supporters of Hallyu and Korea–Japan Relations1. (August 2014) - Oh, Ingyu; Lee, Choong‐Mook
<x xml:space="preserve">Abstract</x> Many researchers agree that Hallyu (the Korean Wave) has been pivotal in promoting a positive Korean national image worldwide, including in Japan, due to Hallyu's unique cultural power, which has touched the hearts of many female fans. However, scholars disagree on the effectiveness of Hallyu as a reliable soft power for Korean public diplomacy. The attractiveness of Hallyu seems to have decidedly waned in Japan amid the emergence of the second Abe cabinet, which did not curtail routinized large‐scale anti‐Hallyu demonstrations in Tokyo. Simultaneously, the Abe government is strongly asserting Japan's new identity as a normal state that could maintain a standing army, while openly engaging in territorial disputes with neighbors and denying wartime atrocities through routine cabinet‐level visits to the Yasukuni Shrine. We argue, however, that Hallyu soft power has an enduring impact on the large number of female supporters of Hallyu in Japan, including Abe's spouse, by empowering them in politics and international relations as a new feminine power group. Unlike the traditional patrimonial households, where Japanese fathers inculcate a strong sense of anti‐Korea discourse in their children, the new Hallyu "moms" are now decidedly training their children to be politically neutral and culturally appreciative of Korea. We find that Hallyu, as a cultural alternative to the male‐dominated Japanese pop culture, is gaining unremitting popular support among Japanese women who are disgruntled over Japan's "lost decades."